Understanding English Terms in the Time of the COVID-19 Pandemic to Teachers and Students Raudhatul Ulum Education Foundation Riduan, Dusun XII Celawan Village, Pantai Mirrin District, Serdang Bedagai Regency - Loebis, Roma Ayuni Aminoeddin; Syaifuddin; Dirmansyah (Talenta Publisher, 2022)
This Community Service activity is understanding English terms during the Covid-19 pandemic to Teachers and Students of the Raudhatul Ulum Riduan Education Foundation, Hamlet XII, Celawan Village, Pantai Cermin District, Serdang Bedagai Regency. As it is known that in early March 2020, the Corona Virus (Covid-19) outbreak began to spread to Indonesia. The epidemic, which originally came from China, is an epidemic that spreads easily, so the WHO (World Health Organization) has issued many recommendations and instructions to the world to curb this epidemic. Because WHO is a world health organization, the terms issued are of course in English. For people in Indonesia, especially those who do not understand English, of course these terms sound foreign. Even though these terms contain important information and advice in this Covid-19 pandemic situation. The final goal to be achieved in this service is the understanding of teachers and students of these English terms so that they can fully implement the suggestions and instructions contained in these English terms.